Management of resources in a federal emergency hospital during the COVID-19 pandemic - Elaine Cristine da Conceição Vianna; Luana Cardoso Pestana; Isabella Barbosa Meireles; Ricardo de Mattos Russo Rafael; Maria Helena Palucci Marziale; Magda Guimarães de Araújo Faria; Cristiane Helena Gallasch (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To describe actions taken by the organizational management of an emergency service due to the COVID-19 pandemic, determined according to the prevalence of cases of infection by the coronavirus, severe acute respiratory syndrome, and flu-like illnesses. Methods: Experience report based on a retrospective analysis of the attention for respiratory syndromes in the first semester of 2019 and 2020, in addition to an analysis of documents from the institutional protocols of a federal emergency service. Development: An increase in the number of attendances was observed, representing 7.25% and 19.4% of cases in 2019 and 2020, respectively. This was due to the creation of the Crisis Office, including a multidisciplinary team created to elaborate the plan of action, changes in the physical structure and in the work processes, and training sessions. Final considerations: It became clear that the planning, coordination of actions based on the decisions of the Crisis Office, and the dissemination of reliable information, taking into consideration a focal point, were essential for the organization, management of the emergency service, and protection to the workers.